How do labor markets affect crime? New evidence on an old puzzle - David B. Mustard (Institute for the Study of Labor (IZA), 2010)
For nearly 50 years academics have been studying how labor markets affect crime. The initial interesting and important theoretical and empirical work generated substantial interest in studying crime among economists, in particular, and scholars in the social sciences more broadly. This literature, which is decades old and contains hundreds of papers, is characterized by an intriguing puzzle - the large gap between the theory and empirical work. While the hypothesis that growing labor markets reduce crime seems obvious and is widely accepted by many policy makers and academics, empirical results fail to show consistent evidence in support of this theory. The primary contribution of this chapter is to document how recent research - primarily since the late 1990s - makes substantial progress in resolving this disconnect between the theory and empirics. To accomplish this goal, I discuss a few very important empirical problems that until the last 10 years have not been systematically addressed. The central conclusion of this chapter is that recent research that addresses these important questions consistently provides evidence to buttress the contention that labor market opportunities have important effects on crime, especially property crime.
Keywords: J2; K14; K42; 330; Crime; labor markets; unemployment; wages; Kriminalität; Arbeitsmarkt; Arbeitslosigkeit; Lohn; Erwerbstätigkeit; Empirische Methode